Analisis Implementasi Kurikulum Merdeka dalam Meningkatkan Profil Pelajar Pancasila - Hermawati; Galih Orlando; Khairul Fahmi Lubis; Syahrin Pasaribu; Mariani Siregar (Insan Zenius Ilmiah, 2026)
The Merdeka Curriculum is an educational policy designed to address the challenges of 21st-century learning by emphasising the strengthening of character and student competencies. One of the main focuses of the Merdeka Curriculum is the strengthening of the Pancasila Student Profile as a reflection of Indonesian students who are faithful, devoted to God Almighty, noble in character, independent, critical thinkers, creative, cooperative, and globally diverse. This research aims to analyse the implementation of the Merdeka Curriculum in enhancing the Pancasila Student Profile in educational units. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research results show that the implementation of the Merdeka Curriculum through project-based learning, differentiated instruction, and strengthening school culture can encourage the development of students' character and competencies in accordance with the dimensions of the Pancasila Student Profile. However, several obstacles are still found, such as teacher readiness, limited facilities, and uneven understanding of the concept. Therefore, continuous support and improvement of educators' competencies are needed to ensure the optimal implementation of the Merdeka Curriculum.